A Critical Review Study on Role of Shirodhara in Twakvikar - Payal R Patel (AYUSHDHARA, 2025)
Shirodhara, a traditional Ayurvedic therapy, involves the rhythmic pouring of medicated liquids over the forehead, primarily aimed at stress management and relaxation. Its potential in addressing Twakvikar (skin disorders) like eczema, psoriasis, and acne, linked to Pitta and Vata dosha imbalances, is noteworthy. By alleviating stress, pacifying Doshas, and enhancing systemic balance, Shirodhara contributes to managing these conditions holistically, emphasizing the mind-body connection. Clinical studies suggest its role in enhancing natural detoxification processes and regulating the hypothalamus and limbic system, reducing psychological stress and hormonal imbalances underlying many skin disorders. Shirodhara’s dual impact on mental and physical health, combined with its ability to improve blood circulation and promote relaxation, supports skin rejuvenation. Medicated oils like Ksheeradhara and Tailadhara nourish and heal inflamed skin, making Shirodhara a valuable adjunct in managing chronic or stress-induced Twakvikar.